Coprescription of QT interval-prolonging antipsychotics with potentially interacting medications in Thailand - Waleekhachonloet, Onanong (Ther Adv Drug Saf, 2019)
BACKGROUND: The US FDA has designated pimozide, thioridazine, and ziprasidone as contraindicated for patients at risk of QT interval prolongation, and assigned haloperidol, olanzapine, paliperidone, quetiapine, and risperidone as associated with a significant risk of QT prolongation. This study aimed to examine trends and hospital variations in concomitant prescribing among these eight selected antipsychotics, and coprescription with interacting drugs known to increase QT prolongation risk. METHODS: Data on outpatient antipsychotic prescriptions during 2012–2015 were obtained from 16 general hospitals and 10 university hospitals nationwide. A time-series analysis was used for estimating trends in coprescription that led to drug interactions. RESULTS: Coprescribing among the eight antipsychotics ranged from 7.5% for quetiapine to 33.1% for thioridazine. The rate of coprescription with contraindicated interacting drugs was 9.7% for thioridazine and 21.9% for pimozide, and increased by 1.1 and 1.4 percentage points (% pt.) yearly for thioridazine in general and university hospitals, respectively. Coprescribing with interacting drugs with precautions was 2.8% for quetiapine, 7.4% for ziprasidone, and 27.9% for risperidone; these percentages increased yearly by 1.7% pt. for ziprasidone and 2.6% pt. for risperidone in general hospitals, as well as by 1.0% pt. for risperidone in university hospitals. The median proportion of patients exposed to a QT-prolonging interaction was 12.3% across hospitals (interquartile range, 9.9–19.5%). Wide interhospital variation was found in percentages of drug interactions among patients receiving thioridazine, ziprasidone, paliperidone, or olanzapine in general hospitals, and among patients receiving paliperidone or pimozide in university hospitals. CONCLUSIONS: Coprescription of antipsychotics with interacting drugs that could increase the risk of QT prolongation was common in Thailand, and thioridazine, ziprasidone, and risperidone showed increasing trends. We urge the incorporation of a unified list of QT-prolonging antipsychotics and interacting drugs into a computerized drug interaction warning system, and existing national rational drug use campaigns should cover this important issue.